Shari’ah credit instrument and banks’ credit risk: The case of Islamic banks / Farihana Shahari - Farihana, Shahari (2017)
The concept of profit and loss sharing (PLS) is the main idea for Islamic banking and financing operation. PLS-based financing is the most recommended tool to be used in structuring the Islamic banks’ credit instrument. The Shari’ah validity of PLS-based financing is accepted by all scholars and researchers. However, the utilization of this concept within the Islamic banks’ financial operation is very limited. Islamic banks prefer to use non-PLS based financing (trade and lease based) due to the fixed and guaranteed return. PLS-based financing is less preferable to the Islamic banks, because uncertain return in PLS-based financing causes high credit risk. This argument contradicts with the theory of PLS which claims that PLS-based financing is able to minimize the credit risk and improve the bank’s performance. The theory of PLS has not been empirically justified in the earlier studies, rather there are some general discussion on the credit risk of Islamic financing. In order to fulfill the gap between theory and practice of Islamic banks, this thesis aims to investigate the issue of credit risk in Islamic banks. By considering the PLS-based financing as Islamic bank’s Shari’ah credit instrument, three issues are raised in this thesis. First, the credit risk associated with Islamic banks’ credit instruments. Second, the relationship between Shari’ah credit instrument and credit risk. Third, the impact of Shari’ah credit instrument on the performance of Islamic bank. To empirically justify the raised issues, this research has selected 40 Islamic banks from 12 different countries. The variance-covariance of Value-at-Risk (VaR) technique has been used to examine the credit risk associated with the credit instruments of Islamic banks. The result indicates that Islamic banks face more bad debt loss in the non-PLS based financing. It also shows that Islamic banks face more credit risk in the non-PLS credit instrument. Furthermore, the Generalized Method of Moments (GMM) is employed to investigate the effect of Shari’ah credit instrument on the credit risk and performance of Islamic banks. The result shows that Shari’ah credit instrument is negatively related with Islamic banks’ credit risk and positively related with the performance. The findings of this research offer several policy implications. The results have pointed out the capability of PLS based financing in minimizing credit risk and improving performance of Islamic banks. The findings are consistent with the theory of PLS which requires labor, risk and skills for the financing activities and helps to reduce the credit risk and improve the performance of financial institutions. The result of this research can be used as a reference for the Islamic banks to adopt PLS based financing instead of non-PLS based financing in order to gain both financial benefits and satisfaction of Allah SWT.